KONSERWATYŚCI POLSCY A REFORMA USTAWODAWSTWA WYBORCZEGO GALICJI NA POCZĄTKU XX WIEKU - Bułachtin, Maksym A. (Zeszyty Prawnicze, 2017)
Polish Conservatives and Reform of the Electoral Law of Galicia at the Beginning of XXth Century Summary The democratization of the political system of the Austro-Hungary at the turn of XIXth and XXth century accelerated the process of political changes. In these circumstances Polish conservatives were seriously bothered about the possibility of weakening not only the influence of the great land owners on the political life of Galicia but also diminishing of their role in shaping „Polish policy” in the whole monarchy. Moreover they were anxious about loosing the position of the party in the political life. Nevertheless the Cracow conservatives (so called „Stańczycy”) admitted the need for democratization of the political institutions and the necessity of concessions from the side of the hitherto governing elite. At the same time they wanted to shape the planned reform of the legislation regarding election to the State Parliament of Galicia (in Polish Sejm Krajowy Galicji) in a way that it ensured the political influence, and as a consequence the protection of interests, to the land owners and other rich social groups. The conservatives also aimed at the protection of Polish interests in a multinational Galicia. They wanted to ensure to Polish inhabitants a strong representation in the State Parliament as well as to guarantee election interests to the Polish minority in the Eastern part of the country, where the majority was composed of the Ukrainians. They also anticipated the smoothing and gradual solving of conflicts of nationalist nature in the country. Therefore they were ready for concessions towards the Ukrainian national demands. Dissimilarly, the conservatives of the Eastern Galicia (so called „podolacy”) did not want the democratization of the political system. They tried to prevent the mass political movements from strengthening. They were against broadening the representation of the Ukrainians in the State Parliament. These disparities led to a crisis between the two groups of the Polish conservatives at the beginning of the XXth century. The policy of the latter group did not have perspectives therefore they had to reconcile themselves with the principles of the reform prepared during the period maybe „when a Cracow conservative Michał Bobrzyński was the deputy of Galicia”.